Globalization, cross-border pollution and welfare - Panos Hatzipanayotou; Sajal Lahiri; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2005)
We construct a two-good general equilibrium model of international trade for two small open economies where pollution from production is transmitted across borders. Governments in both countries impose emission taxes non-cooperatively. Within this framework, we examine the effect of trade liberalization and of changes in the perception of cross-border pollution on Nash emission taxes, emission levels, and welfare.
Keywords: H23; Q28; 330; cross-border pollution; emission taxes; terms of trade; globalization; welfare; Grenzüberschreitende Umweltbelastung; Außenwirtschaftstheorie; Ökosteuer; Nichtkooperatives Spiel; Terms of Trade; Globalisierung; Wohlfahrtseffekt; Theorie